Growth and decline of a penguin colony and the influence on nesting density and reproductive success. Issue 1 (2nd August 2013) - Sherley, Richard B.; Barham, Peter J.; Barham, Barbara J.; Crawford, Robert J. M.; Dyer, Bruce M.; Leshoro, T. Mario; Makhado, Azwianewi B.; Upfold, Leshia; Underhill, Les G.
Abstract: Colonial breeding is characteristic of seabirds but nesting at high density has both advantages and disadvantages and may reduce survival and fecundity. African penguins ( Spheniscus demersus ) initiated breeding at Robben Island, South Africa in 1983. The breeding population on the island increased in the late 1990s and early 2000s before decreasing rapidly until 2010. Before the number breeding peaked, local nest density in the areas where the colony was initiated plateaued, suggesting that preferred nests sites were mostly occupied, and the area used by breeding birds expanded. However, it did not contract again as the population decreased, so that nesting density varied substantially. Breeding success was related positively to the prey available to the breeding birds and negatively to local nest density, particularly during the chick‐rearing period, suggesting a density‐dependence operating through social interactions in the colony, possibly exacerbated by poor prey availability when the breeding population was large. Although nest density at Robben Island was not high, nesting burrows, which probably reduce the incidence of aggressive encounters in the colony, are scarce and our results suggest that habitat alteration has modified the strength of density‐dependent relationships for African penguins. Gaining a better understanding of how density dependence affects fecundity and population growth rates in colonial breeders is important for informing conservation management of the African penguin and other threatened taxa.